Underwater noise exposure induces auditory threshold shifts and metabolomic alterations in the inner ear endolymph of European sea bass - Laura Rojas; Andreas Ruser; Johannes Baltzer; Clément Crouzet; Joseph Schnitzler; Ursula Siebert; Maria Morell (Environmental Pollution, 2026)

Hearing thresholds in European sea bass (Dicentrarchus labrax): new insights into auditory sensitivity - Laura Rojas; Andreas Ruser; Johannes Baltzer; Clément Crouzet; Michael Schlachter; Joseph Schnitzler; Ursula Siebert; Maria Morell (Fish Physiology and Biochemistry, 2026)
Expanding our understanding of auditory sensitivity in fishes is essential not only for advancing sensory biology, but also for assessing the impact of underwater noise on marine life. However, knowledge remains limited for many ecologically and commercially relevant marine species, particularly auditory generalists like the European sea bass ( Dicentrarchus labrax ). In this study, we used auditory evoked potentials (AEPs) to measure hearing thresholds in 114 juvenile European sea bass across six frequencies (100–600 Hz), representing the largest dataset of its kind for this species. Our results revealed a U-shaped audiogram with highest sensitivity at 300 Hz (mean threshold: 116.8 ± 3.3 dB re 1 µPa), and thresholds up to 22 dB lower than previously reported. These findings suggest that D. labrax has higher auditory sensitivity than previously assumed. We also documented significant interindividual variability in hearing thresholds, particularly at lower frequencies, highlighting the importance of large sample sizes to capture natural variation. These baseline data provide a valuable reference for future studies on acoustic ecology, effects of noise exposure, and welfare optimization in aquaculture settings, and emphasize the need for further auditory research in marine fish species.

Evaluating the extent and impact of the extreme Storm Gloria on Posidonia oceanica seagrass meadows - Candela Marco-Méndez; Núria Marbà; Ángel Amores; Javier Romero; Mario Minguito-Frutos; María García; Jordi F. Pagès; Patricia Prado; Jordi Boada; José Luis Sánchez-Lizaso; Juan Manuel Ruiz; Gregori Muñoz-Ramos; et al. (Science of The Total Environment, 2024)

Ultrastructure of the organ of Corti in harbor seals (Phoca vitulina) - Laura Rojas; Martin Haulena; Colleen Reichmuth; Björn Busse; L. Aurora Ramos-Garduño; Oscar Rico-Chávez; Ursula Siebert; Maria Morell (Frontiers in Marine Science, 2023)
Ultrastructural descriptions of the inner ear of highly sound-dependent mammalian species are lacking and needed to gain a better understanding of the hearing sense. Here, we present the first morphometric descriptions of the sensory cells of the inner ear in the harbor seal ( Phoca vitulina ), a mammal with broadly sensitive amphibious hearing. Scanning electron micrographs of the apical surface of the outer hair cells (OHCs) and inner hair cells (IHCs) within the organ of Corti were obtained from five individuals and analyzed by linear and geometric morphometrics. Measurements were taken at regular locations along the cochlea. The spiral shape of the seal cochlea contained two and a half turns. The organ of Corti had an average length of 27.7 mm with 12,628 OHCs (12,400-12,900). Six linear morphometric parameters showed significant patterns of change associated with their location within the cochlear spiral. Likewise, these trends were similarly expressed in cell configuration (cell blocks with 57 landmarks in 12 representative cells) revealed by geometric morphometry. Cell configuration varied predictably with position in the cochlea according to clustering analyses and Procrustes ANOVA (F= 25.936, p<0001). Changes associated with OHCs were primarily responsible for observed changes in cell configuration. An integration trend in cell shape change was also observed in which IHCs and OHCs share features in their morphological variation by the two-block partial least squares analysis (CR=0.987, p<0.001) and the modularity hypothesis (CV=0.99, p=0.05). These descriptive and quantitative findings provide a baseline for the morphology and morphometry of the sensory cells of the organ of Corti in harbor seals, allowing for comparisons between normal and pathological features. This initial morphological description should enable the correlation between position, morphometric features, and frequency coding along the spiral of the inner ear in this species, whose hearing ability is well studied.

Fatal aspergillosis and evidence of unrelated hearing loss in a harbor porpoise (Phocoena phocoena) from the German Baltic Sea - Simon Rohner; Maria Morell; Peter Wohlsein; Julian Stürznickel; Eva B. Reiter; Annika Jahnke; Ellen Prenger-Berninghoff; Christa Ewers; Grit Walther; Lotte C. Striewe; Antonio Virgilio Failla; Ursula Siebert (Frontiers in Marine Science, 2022)
Detailed post-mortem investigations including the auditory pathway are needed to advance our understanding of how underwater noise and other stressors affect hearing in cetaceans. A 12-year-old female porpoise ( Phocoena phocoena ) stranded alive in June 2021 at the German Baltic Sea coast and died some hours later. The most significant pathological findings were lesions caused by a severe aspergillosis that spread from the lung and pulmonary lymph node to the cerebellum. Based on molecular sequencing, the fungus was identified as Aspergillus fumigatus. Severe pyogranulomatous and necrotizing inflammation was diagnosed in the lung and the associated lymph node. In the left part of the cerebellum, focal, severe purulent and necrotizing meningoencephalitis with intralesional fungal structures was confirmed histologically. In addition, multifocal, severe, chronic, granulomatous, and eosinophilic gastritis with intralesional parasite structures was found in the stomach. Parallel stripes (linear skin markings) were detected along the caudal part of both body sides, which have not been previously described for harbor porpoises. Inner ear analysis revealed evidence of focal loss of outer hair cells in several regions from 120 to 580 µm from the apex of the right cochlea using immunofluorescence. The evidence of low-frequency hearing impairment was compatible with noise-induced hearing loss. This is the first case of concurrent presumptive noise-induced hearing loss and unrelated aspergillosis in a free-ranging harbor porpoise.

Pathological findings in stranded harbor porpoises (Phocoena phocoena) with special focus on anthropogenic causes - Lonneke L. IJsseldijk; Mardik F. Leopold; Lineke Begeman; Marja J. L. Kik; Lidewij Wiersma; Maria Morell; Elisa L. Bravo Rebolledo; Thierry Jauniaux; Hans Heesterbeek; Andrea Gröne (Frontiers in Marine Science, 2022)
Humans impact natural systems at an unprecedented rate. The North Sea is one of the regions in the world with the highest levels of anthropogenic activity. Here, the harbor porpoise ( Phocoena phocoena ) is an abundant species and is often regarded as an ecosystem sentinel. A post-mortem surveillance program was established in the Netherlands aimed at increasing knowledge of the effects of human activities on harbor porpoises. In this study, we describe the pathological findings related to anthropogenic and natural causes of death categories in 612 harbor porpoises that stranded between 2008 and 2019, and assess their relations to age, sex, season, and location. The largest anthropogenic category was bycatch (17%), with mainly juveniles affected and peak periods in March and September–October. Other, infrequently diagnosed anthropogenic causes of death were trauma (4%), largely most likely due to ship collisions, and marine debris ingestion and entanglement (0.3%). The risk of dying from anthropogenic causes was highest for juveniles. Lesions compatible with noise-induced hearing loss were investigated in carcasses which were fresh enough to do so (n = 50), with lesions apparent in two porpoises. Non-direct human-induced threats included infectious diseases, which were by far the largest cause of death category (32%), and affected mainly adults. Also, gray seal ( Halichoerus grypus ) attacks were a frequently assigned cause of death category (24%). There were more acute predation cases in the earlier study years, while porpoises with lesions that suggested escape from gray seal attacks were diagnosed more recently, which could suggest that porpoises adapted to this threat. Our study contributes to understanding porpoise health in response to persisting, new, emerging, and cumulative threats. Building up such knowledge is crucial for conservation management of this protected species.

Uncrewed Ocean Gliders and Saildrones Support Hurricane Forecasting and Research - Travis Miles; Dongxiao Zhang; Gregory Foltz; Jun Zhang; Christian Meinig; Francis Bringas; Joaquin Triñanes; Matthieu Le Hénaff; Maria Aristizabal Vargas; Sam Coakley; Catherine Edwards; Donglai Gong; et al. (Oceanography, 2021)

Mesolithic human remains at Cueva de Nerja (Málaga, Spain): anthropological, isotopic and radiocarbon data - Luis-Efren Fernández; José Luis Sanchidrián; Sylvia A. Jiménez-Brobeil; Gerard Remolins; Marta Díaz-Zorita; Berta Morell; Maria Eulàlia Subirà; Diego López-Onaindía; Rosa M. Maroto; María G. Roca; Carmen M. Román; Francisco Javier Santos; et al. (Archaeological and Anthropological Sciences, 2020)

Human diet and the chronology of neolithic societies in the north-east of the Iberian Peninsula: the necropolises of Puig d’en Roca and Can Gelats (Girona, Spain) - Juan F. Gibaja; Maria Fontanals-Coll; Stephanie Dubosq; F. Xavier Oms; Anna Augé; Francisco Javier Santos; Berta Morell; M. Eulàlia Subirà (Archaeological and Anthropological Sciences, 2017)